Pertanggungjawaban Perdata Rumah Sakit Dalam Hal Penolakan Pasien Pada Keadaan Gawat Darurat - Hanifah Romadhoni; Arief Suryono (Fakultas Hukum Universitas Sebelas Maret, 2021)
This article aims to find out the civil liability of the hospital for the refusal actions taken by health workers for poor patients in emergencies. This legal research includes a type of normative legal research that is prescriptive. Sources of legal materials used are primary and secondary legal materials .. Data collection techniques used are literature studies or document studies, furthermore technical analysis used is a deductive method .. The results of research that the authors do get the conclusion that the action of health workers who refused the hospital Poor patients in emergency situations are acts against the law due to negligence. Therefore the hospital is charged with civil responsibility for the negligence of health personnel in hospitals that refuse poor patients in emergency situations that cause harm to a person / patient based on Article 46 of Law No. 44 on Hospital, the doctrine of respondeat superior, and vicarious liability principle. The manifestation of the hospital's civil liability is to compensate for the losses suffered by the patient.